Ultrasonic-Supercritical CO2-Assisted Extraction and Component Analysis of Navel Orange Peel Pigment - Yu, Xianchun; Wu, Ying; Sun, Delin; Tian, Tian (Asian Journal of Chemistry, 2015)
Navel orange peel pigment was extracted using an ultrasonic-supercritical CO2-assisted method. Extraction process was optimized using response surface methodology and pigment components were analyzed. Results of infrared spectroscopy and second-derivative analysis indicated that navel orange peel pigment principally contained aromatic ring, sugars and alkenes. Response surface methodology identified that the optimized conditions to obtain 72.34 % yield were as follows: ultrasonic power, 250 W; supercritical CO2 flow rate, 20 L/h; extraction pressure, 7.7 MPa; temperature, 53 °C; and time, 38 min.